Fungal Carboxymethyl Chitosan-Impregnated Bacterial Cellulose Hydrogel as Wound-Dressing Agent - Maduru Suneetha; So-Yeon Won; Sun Mi Zo; Sung Soo Han (Gels, 2023)
Bacterial cellulose (BC) produced by Gluconoacetobacter hansenii is a suitable polymeric fiber network for wound-dressing purposes, but its lack of antibacterial properties limits it from healing bacterial wounds. We developed hydrogels by impregnating fungal-derived carboxymethyl chitosan to BC fiber networks using a simple solution immersion method. The CMCS–BC hydrogels were characterized using various characterization techniques such as XRD, FTIR, water contact angle measurements, TGA, and SEM to know the physiochemical properties. The results show that the impregnation of CMCS into BC fiber networks greatly influences BC’s improving hydrophilic nature, which is crucial for wound healing applications. Furthermore, the CMCS–BC hydrogels were studied for biocompatibility analysis with skin fibroblast cells. The results revealed that by increasing the CMCS content in the BC, biocompatibility, cell attachment, and spreading capacity also increase. The antibacterial activity of CMCS–BC hydrogels is shown using the CFU method against Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus). As a result, the CMCS–BC hydrogels exhibit more suitable antibacterial properties than those without BC due to the CMCS having amino groups that enhance antibacterial properties. Therefore, CMCS–BC hydrogels can be considered suitable for antibacterial wound dressing applications.